C. G. Jung’s life and major works - GUDAITĖ, GRAŽINA (Psichologija, 1997)
The article presents a short biography of C. G. Jung and the analysis of major theory constructs.
Keywords: Jung; biography; collective unconscious; archetypes; individuation